6x-12=4(x+7)

Simple and best practice solution for 6x-12=4(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-12=4(x+7) equation:


Simplifying
6x + -12 = 4(x + 7)

Reorder the terms:
-12 + 6x = 4(x + 7)

Reorder the terms:
-12 + 6x = 4(7 + x)
-12 + 6x = (7 * 4 + x * 4)
-12 + 6x = (28 + 4x)

Solving
-12 + 6x = 28 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-12 + 6x + -4x = 28 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-12 + 2x = 28 + 4x + -4x

Combine like terms: 4x + -4x = 0
-12 + 2x = 28 + 0
-12 + 2x = 28

Add '12' to each side of the equation.
-12 + 12 + 2x = 28 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = 28 + 12
2x = 28 + 12

Combine like terms: 28 + 12 = 40
2x = 40

Divide each side by '2'.
x = 20

Simplifying
x = 20

See similar equations:

| 2cos^2(x)-4cos(x)=0 | | (9x^2-7)*(9x^2+7)= | | 2/9-3 | | 8P+4Q=68 | | x^2+ln(-x+4)= | | 2(x+5)=8is | | 25s^2-81=0 | | 13=5-13+3c | | 2x+-5y+9=0 | | 13=5+4a | | 7428=p*6 | | 13-5=4a | | f(x)=-120+5x | | g+g+g=(1+g) | | 1-12=z/-4 | | -15x+25=220 | | 9t^2-20t-21=0 | | kx^2+3x-k+5=0 | | x^2+2xy=8 | | x-7=-2+5 | | (a^2-1/2*a)^5 | | -5+6=4+x | | 7-3x=6x-15 | | 9-6=3+5x | | -2z^3+9z+27i=0 | | F-6=98 | | 3x+(3+4)=8+(x-5) | | c=120+60 | | 2x+4x-7x+12=2(x-10) | | 8(n-5)=48 | | 2y+24=4y-6 | | 36=2(x-5) |

Equations solver categories